Repetitive element hypermethylation in multiple sclerosis patients. Issue 1 (December 2016) - Neven, K.; Piola, M.; Angelici, L.; Cortini, F.; Fenoglio, C.; Galimberti, D.; Pesatori, A.; Scarpini, E.; Bollati, V.
Abstract Background Multiple sclerosis (MS) is a complex disorder of the central nervous system whose cause is currently unknown. Evidence is increasing that DNA methylation alterations could be involved in inflammatory and neurodegenerative diseases and could contribute to MS pathogenesis. Repetitive elementsAlu, LINE-1 andSAT- α, are widely known as estimators of global DNA methylation. We investigatedAlu, LINE-1 andSAT- α methylation levels to evaluate their difference in a case–control setup and their role as a marker of disability. Results We obtained blood samples from 51 MS patients and 137 healthy volunteers matched by gender, age and smoking. Methylation was assessed using bisulfite-PCR-pyrosequencing. For all participants, medical history, physical and neurological examinations and screening laboratory tests were collected. All repetitive elements were hypermethylated in MS patients compared to healthy controls. A lower Expanded Disability Status Scale (EDSS) score was associated with a lower levels ofLINE-1 methylation for 'EDSS = 1.0' and '1.5 ≤ EDSS ≤ 2.5' compared to an EDSS higher than 3, whileAlu was associated with a higher level of methylation in these groups: 'EDSS = 1.0' and '1.5 ≤ EDSS ≤ 2.5'. Conclusions MS patients exhibit an hypermethylation in repetitive elements compared to healthy controls.Alu andLINE-1 were associated with degree of EDSS score. Forthcoming studies focusing on epigenetics and the multifactorial pathogenetic mechanism of MS could elucidate these links further.